2008
DOI: 10.1007/s11224-008-9391-y
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio and density functional theory study on the mechanism for the reaction of OH with 2-ethylfuran

Abstract: The mechanism of the reaction of OH ? 2-ethylfuran has been investigated using the G3MP2 and G3MP2B3 levels of theory. The geometric parameters of all species involved in the reaction have been optimized at the MP2 and B3LYP levels of theory with 6-311G(d,p) basis set. The overall profile of doublet potential energy surface (PES) for the OH ? 2-ethylfuran reaction has been constructed using the G3MP2 and G3MP2B3 methods. The results show that the addition-elimination mechanism dominates the OH ? 2-ethylfuran r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, for furans and THFs with longer side chains (ethyl and larger) neither kinetic models nor experimental data are available. Only for 2-ethylfuran (2-EF), Zhang et al [11] performed ab-initio calculations for H-abstraction from the fuel molecule by the hydroxyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…However, for furans and THFs with longer side chains (ethyl and larger) neither kinetic models nor experimental data are available. Only for 2-ethylfuran (2-EF), Zhang et al [11] performed ab-initio calculations for H-abstraction from the fuel molecule by the hydroxyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the formation of a pre-reaction complex in the addition pathways is effective only for temperatures below 550 K. Therefore, the authors inferred that OH addition paths are active under low temperatures, while H-abstraction channels become more dominant under typical combustion conditions. In addition to the studies focusing on individual fuels such as furan, 2-MF and 2,5-DMF, another group of studies focused on the chemical kinetics of alkyl furan formation and decomposition [124][125][126][127][128]. One of such efforts is a study by Simmie and Curran [124], in which the room-temperature enthalpies of formation of 2,3-dimethyl-, 2,4-dimethyl-, 3,4-dimethyl-, 2-methyl-, 3-methyl-, 2-ethyl-and 2-vinylfurans were calculated.…”
Section: Quantum Chemical Kinetic Calculationsmentioning
confidence: 99%
“…The results show that the calculated values for the room-temperature enthalpies of formations exhibit good agreement with experimental results. Moreover, Zhang et al [126] performed quantum chemical kinetic calculations to understand the reaction OH + 2-ethylfuran (2-EF). The results revealed that the dominant mechanism for the OH + 2-EF reaction is the addition-elimination mechanism, while the major products are identified as CH 3 CH 2 C(OH)CHCHCHOH and CH 3 CH 2 COCHCHCHOH.…”
Section: Quantum Chemical Kinetic Calculationsmentioning
confidence: 99%
“…2‐Ethylfuran has been chosen for this study based on its role as a primary and secondary pollutant emitted into the atmosphere from both anthropogenic and biogenic sources . This alkylfuran also has potential to be a next‐generation biofuel based on the promising characteristics of the alkylfurans 2‐methylfuran and 2,5‐dimethylfuran .…”
Section: Introductionmentioning
confidence: 99%
“…2-Ethylfuran has been chosen for this study based on its role as a primary and secondary pollutant emitted into the atmosphere from both anthropogenic and biogenic sources. [15,21,[23][24][25] This alkylfuran also has potential to be a next-generation biofuel based on the promising characteristics of the alkylfurans 2-methylfuran and 2,5-dimethylfuran. [5,13,26] Villanueva et al [15] has provided insight on the oxidation of 2EF using Fourier Transform Infrared (FTIR) absorption spectroscopy and solid-phase microextraction gas chromatography by flame ionization, electron capture and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%